Empowering Students' Vocabulary Through Vocab-O-Gram at Senior High School level - Hamid Ismail; Rina Asrini Bakri; Saiful Saiful; Yustina Kurnia (Faculty of Education and Teacher Training of UIN Palopo, 2022)
This study aims to determine whether the Vocab-O-Gram strategy can increase students' vocabulary. This study's methodology is pre-experimental. In this situation, the aforementioned strategy assisted the students in enhancing their motivation to lift new vocabulary. Students at class science II (two) SMA Bajiminasa Makassar as the population in this research. 20 students participated in the study's sample, which was created using a representative sampling technique in which only a small number of students were selected as the study's potential subjects. The data in question was then examined in the percentage format, along with ratio and percentage analysis and t-test. The results of the data analysis show that there are differences between the two tests namely the pre-test and post-test, which are distinguished by the fact that the test taken after the first one is larger than the test taken before it (8.35 > 6.05). The t-test result was more significant than the t-table result (22.11 > 2.039) at the significance level of 0.05 per cent. The data that was obtained by the researchers and entered into the table shows that the ratio of the initial rate to the final rate is larger. It can be inferred that the Vocab-O-Gram strategy was successful in raising the test scores of the second-grade students at SMA Bajiminasa Makassar.